Validação de conteúdo da Escala Subjetiva de Carga Mental de Trabajo (ESCAM) para o português do Brasil - Cerdótes, Ana Luiza Parcianello (2020)
In the last few decades, there has been an increase in mental health related disorders to the detriment of physical diseases in the workpleace. This study aimed to validate, in terms of contente, the Subjective mental Workload Scale (ESCAM) for Brazilian Protuguese. ESCAM is a Spanish scale for measuring mental workload (CMT). It consists of 20 items distributed in five dimensions. This is a methodological study of contente validation. The contente and face validation incluid semantic, conceptual and item equivalence. Authorization was requested dor the authors and, soon after, the process started with the translation of the original instrument (OI), the synthesis of the translations, the back-translation, synthesis II by consensus commitee (CC), painel of experts (PE), pilot test (PT) and final report for the authors of the scale. The PE was composed by the participation of seven experts and the PT by 33 graduate students from the Prosgraduate Program in Nursing (PPGENF) and by 40 graduate students in the second round. Data collection was performed through eletronic mail, using available Technologies, such as google forms. To evaluate the PT, the PASW Statistic program (Predicitive analytics Software, from SPSS Inc, Chicago, USA) version 18.0 for Windows was used. ESCAM was subjected to the calculation of the contente validity index (CVI) and percentage of agrément. In all stages of the process, suggestions werw incorporated and the necessary items werw reassessed. In translations and back-translations, ESCAM presented no or little difficulty in translating most items. In the PE, CVI between 0,97 to 1,00 was obtained na theagreement in the PT varied from 90% to 100%. The authors evaluated the items, made contributions and appoved the final version of ESCAM. The scale presented contente validity for brazilian portuguese.